Medication adherence in first episode psychosis: the role of pre‐onset subthreshold symptoms - Daneault, J.‐G.; Maraj, A.; Lepage, M.; Malla, A.; Schmitz, N.; Iyer, S. N.; Joober, R.; Shah, J. L. (Acta psychiatrica Scandinavica, 2019)
Objective The experience of pre‐onset subthreshold psychotic symptoms (STPS, signifying a clinical high‐risk state) in first episode psychosis (FEP) predicts poorer outcomes during treatment, possibly through differential adherence to medication. We explored whether adherence differs between FEP patients with and without pre‐onset STPS. Methods Antipsychotic medication adherence was compared in 263 STPS+ and 158 STPS− subjects in a specialized early intervention program for FEP. Data were gathered from a larger observational study conducted between 2003 and 2016. STPS status, sociodemographic, and baseline clinical variables were tested as predictors of non‐adherence using univariate and multivariate logistic regressions. Time to onset of non‐adherence was analyzed using Kaplan–Meier curves. The same predictors were tested as predictors of time to onset of non‐adherence using Cox regression models. Results Medication non‐adherence was higher in STPS+ participants (78.9% vs. 68.9%). STPS status (OR 1.709), substance use disorder (OR 1.767), and milder positive symptoms (OR 0.972) were significant baseline predictors of non‐adherence. Substance use disorder (HR 1.410), milder positive symptoms (HR 0.990), and lack of contact between the clinical team and relatives (HR 1.356) were significant baseline predictors of time to non‐adherence. Conclusion FEP patients who experience pre‐onset STPS are more likely to be non‐adherent to antipsychotic medication over 2 years of intervention. FEP programs should routinely evaluate pre‐onset symptomatology to deliver more personalized treatments, with emphasis on engaging both patients and family members from the beginning of care.